2019
DOI: 10.18535/jmscr/v7i4.149
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Animal Bite Cases at Anti-Rabies Clinic of Tertiary Care Hospital: A Record Based Study

Abstract: Rabies is a fatal disease caused by Lysa virus. Human cases occur due to dog bites in 99% of cases. Data on animal bite cases are very useful for planning for prevention of rabies for the authorities. This record based study was undertaken to study the profile of animal bite cases attending anti rabies clinic of tertiary hospital in one year. A total of 6399 cases were registered in one year with 68.32% male, 63.45% category III, 71.71% belong to urban areas. Animal bite cases are on rise in Kashmir and need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The dominant category of bite in this study was observed to be category II (60%). This was in consonance with the studies done by Sangeetha et al 8 and Amrutha et al, 4 whereas, in a few other studies done by Venu Shah et al, 12 Samreen et al 13 and Kumar et al, 14 the victims mostly had category III animal bite.…”
Section: Discussionsupporting
confidence: 87%
“…The dominant category of bite in this study was observed to be category II (60%). This was in consonance with the studies done by Sangeetha et al 8 and Amrutha et al, 4 whereas, in a few other studies done by Venu Shah et al, 12 Samreen et al 13 and Kumar et al, 14 the victims mostly had category III animal bite.…”
Section: Discussionsupporting
confidence: 87%